An Investigation in Terms of Settlement Geography: Yalova City - Ercan Kazel; Mehmet Bayartan (Coğrafya Dergisi)
This paper discusses Yalova City as a model city from the Republic period to the present day. From a historical perspective, Yalova City, the reasons for its establishment, and its development process are evaluated. The physical geographic characteristics of the city, its economic structure, population, settlement characteristics, and their impact on Yalova are explored. To transfer numerical and verbal information with the basic geographical features of Yalova City, various maps and plans are created by using Geographical Information Systems and remote sensing methods, and it has also been ensured that all data obtained are connected with the location. Yalova has evolved and acquired its identity as a result of its suitable location and the existence of hot springs in its area. Hot springs have a profound effect on the city’s establishment and development. Due to transportation alternatives, proximity to big cities, and other geographical advantages, the field of ornamental plant production flourished in Yalova through tourism. Additionally, after severing administrative ties with Istanbul, Yalova City has become a significant settlement in the region.